A ceramic capacitor dielectric material for energy storage and its preparation method and application

CN117410098BActive Publication Date: 2026-10-23GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311404128.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2026-10-23
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

比较常见的有铅基弛豫铁电体系、钛酸钡基铁电体系等,但是铅基弛豫铁电体体系在生产和应用过程中会对人体和环境造成极大的危害,因此,研究无铅介电陶瓷系统具有重要价值和实际意义

Benefits of technology

[0034](1)本发明采用固相法制备介质材料,工艺简单、对环境无害,且所制得的用于储能的温度稳定型陶瓷型陶瓷电容器介质材料,Sr1.84Ba0.155Sm0.005NaMn0.005Nb4.995O15、Sr1.83Ba0.16Sm0.01NaMn0.01Nb4.99O15陶瓷电容器介质材料能够在-55~150℃的范围内满足(ΔC/C25)≤±15%,达到EIA的X8R标准;Sr1.82Ba0.165Sm0.015NaMn0.015Nb4.985O15、Sr1.81Ba0.17Sm0.02NaMn0.02Nb4.98O15陶瓷电容器介质材料能够在-55~200℃的范围内满足(ΔC/C25)≤±15%,达到EIA的X9R标准;经过铁电测试,发现四种组分的陶瓷都具有良好的储能性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117410098B_ABST
    Figure CN117410098B_ABST
Patent Text Reader

Abstract

The application provides a ceramic capacitor dielectric material for energy storage and a preparation method and application thereof, and belongs to the technical field of electronic materials and devices. 1.85‑2x Ba 0.15+x Sm x NaMn x Nb 5‑x O 15 , wherein the value of x is 0.005, 0.01, 0.015 or 0.02. The ceramic capacitor dielectric material has good temperature stability, excellent energy storage performance, a simple preparation method, and good industrialization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic materials and devices, and in particular to a ceramic capacitor dielectric material for energy storage, its preparation method, and its application. Background Technology

[0002] As a fundamental component of circuit systems, capacitors function to store charge, block DC, filter AC, and provide tuning and oscillation, making them an important type of passive electronic device. Multilayer ceramic chip capacitors (MLCCs) are among the most widely used and consumed types of capacitors in recent years. Due to their wide operating temperature range, small size, wide capacitance range, and ease of surface assembly, they are widely used in industries such as automatic control, computers, and automotive electrical systems. According to the Electronic Industries Association (EIA) standard, an X8R type multilayer ceramic capacitor (MLCC) refers to a capacitor with a capacitance value at 25°C as a reference, and a capacitance change rate (ΔC / C) within a temperature range from -55°C to +150°C. 25 The capacitance change rate (ΔC / C25) is ≤ ±15% when the capacitance value is based on 25℃, within a temperature range of -55℃ to +200℃. The X9R type multilayer ceramic capacitor (MLCC) refers to a capacitor with a capacitance value of 25℃ as a reference, where the capacitance change rate (ΔC / C25) is ≤ ±15%.

[0003] Currently, temperature-stable MLCCs are widely used in various electronic devices. Due to the excessive consumption of fossil fuels, the intermittent and random nature of sustainable energy sources cannot meet peak electricity demand, prompting the rapid development of high-efficiency and high-performance energy storage materials. Compared with traditional batteries and supercapacitors, ceramic capacitors stand out among energy storage devices such as batteries and supercapacitors due to their high operating voltage, ultra-short charge / discharge time, and mechanical / thermal resistance. Common types include lead-based relaxor ferroelectric systems and barium titanate-based ferroelectric systems. However, lead-based relaxor ferroelectric systems pose significant risks to human health and the environment during production and application. Therefore, research on lead-free dielectric ceramic systems is of great value and practical significance. Summary of the Invention

[0004] To overcome the aforementioned deficiencies in the prior art, this invention provides a ceramic capacitor dielectric material for energy storage, its preparation method, and its application. The material adopts a tungsten bronze structure, which helps to expand the structural types of ceramic capacitor materials and reduce the harm caused by lead-based ceramics to human health and the environment.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] On one hand, the present invention provides a ceramic capacitor dielectric material for energy storage, wherein the chemical formula of the ceramic capacitor dielectric material is Sr 1.85-2xBa 0.15+x Sm x NaMn x Nb 5-x O 15 , where x takes the values ​​0.005, 0.01, 0.015 or 0.02.

[0007] Optionally, the capacitance change rate of the ceramic capacitor dielectric material is ≤ ±15%.

[0008] Secondly, this application provides a method for preparing the above-mentioned ceramic capacitor dielectric material for energy storage, comprising the following steps:

[0009] (1) A mixture containing SrCO3, BaCO3, Sm2O3, Na2CO3, MnO2 and Nb2O5 was ball-milled and dried in sequence to obtain sample I;

[0010] (2) Press the sample I into shape and pre-fire it to obtain sample II;

[0011] (3) Grind the sample II into powder, and then perform ball milling, drying, pressing, cold isostatic pressing, sintering, and cooling to room temperature to obtain the ceramic capacitor dielectric material for energy storage.

[0012] Optionally, in step (1), the molar ratio of Sr, Ba, Sm, Na, Mn, Nb and O elements in the mixture is (1.85-2x):(0.15+x):x:1:x:(5-x):15, where x takes the value of 0.005, 0.01, 0.015 or 0.02.

[0013] Optionally, in steps (1) and (3), the ball milling independently uses anhydrous ethanol as the ball milling medium;

[0014] The rotational speed of the ball mill is independently 250–350 r / min;

[0015] The ball milling time is independently 5 to 7 hours.

[0016] Optionally, in steps (1) and (3), the drying temperature is independently 100-150°C;

[0017] The drying time is independently 3 to 5 hours.

[0018] Optionally, in steps (1) and (3), the drying temperature is independently selected from any value of 100℃, 110℃, 120℃, 130℃, 140℃, 150℃ or a range between any two of the above points.

[0019] Optionally, in steps (1) and (3), the drying time is independently selected from any value of 3h, 3.5h, 4h, 4.5h, 5h or a range between any two of the above points.

[0020] Optionally, in step (2), the pre-firing temperature is 800–1200°C;

[0021] The preheating time is 3 to 5 hours.

[0022] Optionally, in step (2), the preheating temperature is independently selected from any value among 800℃, 900℃, 1000℃, 1100℃, and 1200℃, or a range between any two of the above points.

[0023] Optionally, in step (2), the pre-burning time is independently selected from any value of 3h, 3.5h, 4h, 4.5h, 5h or a range between any two of the above points.

[0024] Optionally, in step (3), the pressure of the cold isostatic pressing is 150-250 MPa.

[0025] Optionally, in step (3), the pressure of the cold isostatic pressing is independently selected from any value of 150MPa, 180MPa, 200MPa, 220MPa, 250MPa or the range between any two of the above points.

[0026] Optionally, in step (3), the sintering temperature is 1230–1250°C;

[0027] The sintering time is 5 to 10 hours;

[0028] The heating rate of sample II during the sintering process is 4–6 °C / min.

[0029] Optionally, in step (3), the sintering temperature is independently selected from any value among 1230℃, 1235℃, 1240℃, 1245℃, and 1250℃, or a range between any two of the above points.

[0030] Optionally, in step (3), the sintering time is independently selected from any value of 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of the above points.

[0031] Optionally, in step (3), the heating rate of sample II during the sintering process is independently selected from any value of 4℃ / min, 4.5℃ / min, 5℃ / min, 5.5℃ / min, 6℃ / min or the range between any two of the above points.

[0032] Thirdly, this application provides the application of the above-mentioned ceramic capacitor dielectric material for energy storage in the manufacture of capacitors.

[0033] Compared with the prior art, the beneficial effects of the present invention include:

[0034] (1) This invention uses a solid-state method to prepare dielectric materials, which is simple, environmentally friendly, and produces temperature-stable ceramic capacitor dielectric materials suitable for energy storage, Sr 1.84 Ba 0.155 Sm 0.005 NaMn 0.005 Nb 4.995 O 15 、Sr 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 The dielectric material of ceramic capacitors can meet the EIA X8R standard by satisfying (ΔC / C25) ≤ ±15% within the temperature range of -55 to 150℃; Sr 1.82 Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15 、Sr 1.81 Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15 The ceramic capacitor dielectric material can meet the requirement of (ΔC / C25)≤±15% within the range of -55~200℃, reaching the EIA X9R standard; after ferroelectric testing, it was found that all four ceramic components have good energy storage performance.

[0035] (2) The ceramic capacitor dielectric material provided by the present invention has good temperature stability, excellent energy storage performance and simple preparation method, and has good industrialization and application prospects. Attached Figure Description

[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0037] Figure 1 Sr prepared according to an embodiment of the present invention 1.85-2x Ba 0.15+x Smx NaMn x Nb 5-x O 15 (x = 0.005, 0.01, 0.015 or 0.02) X-ray diffraction pattern of the dielectric material of ceramic capacitor;

[0038] Figure 2 Sr prepared according to an embodiment of the present invention 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 (x = 0.005, 0.01, 0.015 or 0.02) Surface micrographs of the dielectric material of ceramic capacitors (Note: (a) indicates Sr 1.84 Ba 0.155 Sm 0.005 NaMn 0.00 5Nb 4.995 O 15 (a) Surface micrographs; (b) indicates Sr 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 Surface micrographs; (c) indicates Sr 1.82 Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15 Surface micrographs; (d) indicates Sr 1.81 Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15 (Surface micrographs);

[0039] Figure 3 Sr prepared according to an embodiment of the present invention 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 (x = 0.005, 0.01, 0.015 or 0.02) Graph showing the change of dielectric constant of ceramic capacitor dielectric material with temperature;

[0040] Figure 4 For the present invention Sr 1.85-2x Ba 0.15+x Sm x NaMn xNb 5-x O 15 (x = 0.005, 0.01, 0.015, or 0.02) The graph shows the rate of change of capacitance of the dielectric material of a ceramic capacitor as a function of temperature. From the graph, it can be seen that Sr... 1.84 Ba 0.155 Sm 0.005 NaMn 0.005 Nb 4.995 O 15 、Sr 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 The dielectric constant of Sr varies within ±15% from -55℃ to 150℃. 1.82 Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15 、Sr 1.81 Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15 The dielectric constant changes within ±15% from -55℃ to 200℃ (Note: (a) indicates Sr). 1.84 Ba 0.155 Sm 0.005 NaMn 0.005 Nb 4.995 O 15 (a) The rate of change of dielectric constant from -55°C to 200°C relative to room temperature; (b) represents Sr 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 The rate of change of dielectric constant from -55°C to 200°C relative to room temperature; (c) represents Sr 1.82 Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15 The rate of change of dielectric constant from -55°C to 200°C relative to room temperature; (d) represents Sr 1.81 Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15 The rate of change of dielectric constant from -55°C to 200°C relative to room temperature.

[0041] Figure 5 For the present invention Sr 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 (x = 0.005, 0.01, 0.015, or 0.02) Room temperature hysteresis loop test plots of ceramic capacitor dielectric materials. The plots show that all four components exhibit high energy storage performance, with Sr... 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 Its energy storage density is 4.432 J / cm³. 3 The efficiency is 84.3% (Note: (a) indicates Sr 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 (a) Ferroelectric monopole hysteresis loops of four components (x = 0.005, 0.01, 0.015, or 0.02); (b) Represents Sr 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 (x = 0.005, 0.01, 0.015 or 0.02) Total energy storage density, effective energy storage density and efficiency of the four components. Detailed Implementation

[0042] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0043] Unless otherwise specified, the raw materials used in the embodiments of this application are all purchased commercially and used directly without any special treatment.

[0044] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.

[0045] Example 1

[0046] Raw materials SrCO3, BaCO3, Sm2O3, Na2CO3, MnO2, and Nb2O5, all with a purity of 99.99%, were prepared in a stoichiometric ratio as follows: Sr 1.84 Ba 0.155 Sm 0.005 NaMn0.005 Nb 4.995 O 15 The raw materials were placed in a ball mill jar and ball-milled in a high-energy ball mill using zirconia balls as the milling medium. The added raw material mass was 8% of the mass of the milling balls. The mixing and milling time was 6 hours, the rotation speed was 300 rpm, and the milling medium was anhydrous ethanol. The resulting product was dried in an oven at 120℃ for 4 hours, and then pre-sintered at 1000℃ for 4 hours at a heating rate of 5℃ / min. The pre-sintered powder was then crushed, and then high-energy ball-milled for 6 hours with anhydrous ethanol as the milling medium to mix evenly. After drying at 120℃ for 4 hours, it was ground into powder, then pressed into discs, and cold isostatically pressed at 200MPa. The samples were sintered at 1230℃ in an air atmosphere in a high-temperature furnace and held for 6 hours. The heating rate of the samples was 5℃ / min. Finally, the samples were cooled to room temperature with the furnace to obtain a temperature-stable ceramic capacitor dielectric material for energy storage.

[0047] Silver electrodes were sintered onto both sides of the sintered ceramic dielectric material to fabricate a disc capacitor. The relative permittivity of the dielectric material as a function of temperature was then tested and calculated. Within the temperature range of -55 to 150°C, Sr... 1.84 Ba 0.155 Sm 0.00 5NaMn 0.005 Nb 4.995 O 15 The capacitance variation rate of the ceramic material does not exceed ±15%, meeting the X8R standard. 1.84 Ba 0.155 Sm 0.005 NaMn 0.005 Nb 4.995 O 15 Its energy storage density is 3.1 J / cm³. 3 The efficiency is 78.4%.

[0048] Example 2

[0049] Raw materials SrCO3, BaCO3, Sm2O3, Na2CO3, MnO2, and Nb2O5, all with a purity of 99.99%, were prepared in a stoichiometric ratio as follows: Sr 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15The ingredients were placed in a ball mill jar and ball-milled in a high-energy ball mill using zirconia balls as the milling medium. The added raw material was 8% of the mass of the milling balls. The mixing and milling time was 6 hours, the rotation speed was 300 rpm, and the milling medium was anhydrous ethanol. The resulting product was dried in an oven at 120°C for 4 hours, and then pre-sintered at 1000°C for 4 hours at a heating rate of 5°C / min. The pre-sintered powder was then removed, ground, and then high-energy ball-milled for 6 hours with anhydrous ethanol as the milling medium to mix evenly. After drying at 120°C for 4 hours, it was ground into powder, then pressed into discs, and cold isostatically pressed under a pressure of 200 MPa. The discs were then sintered in a high-temperature furnace in an air atmosphere at 1240°C for 6 hours at a heating rate of 5°C / min. Finally, the discs were cooled to room temperature in the furnace to obtain a temperature-stable ceramic capacitor dielectric material for energy storage.

[0050] Silver electrodes were sintered onto both sides of the sintered ceramic dielectric material to form a disc capacitor. The relative permittivity of the dielectric material as a function of temperature was then tested and calculated. Figure 3 As shown, within the temperature range of -55 to 150℃, Sr 1.8 3Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 The capacitance variation rate of the ceramic material does not exceed ±15%, meeting the X8R standard. For example... Figure 5 As shown, Sr 1.83 Ba 0.16 Sm 0.01 NaMn 0.01 Nb 4.99 O 15 Its energy storage density is 4.432 J / cm³. 3 The efficiency is 84.3%.

[0051] Example 3

[0052] Raw materials SrCO3, BaCO3, Sm2O3, Na2CO3, MnO2, and Nb2O5, all with a purity of 99.99%, were prepared in a stoichiometric ratio as follows: Sr 1.82 Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15The raw materials were placed in a ball mill jar and ball-milled in a high-energy ball mill using zirconia balls as the milling medium. The added raw material was 8% of the mass of the milling balls. The mixing and milling time was 6 hours, the rotation speed was 300 rpm, and the milling medium was anhydrous ethanol. The resulting product was dried in an oven at 120°C for 4 hours, and then pre-sintered at 1000°C for 4 hours at a heating rate of 5°C / min. The pre-sintered powder was then removed, ground, and then high-energy ball-milled for 6 hours with anhydrous ethanol as the milling medium to mix evenly. After drying at 120°C for 4 hours, it was ground into powder. Subsequently, it was pressed into discs and cold isostatically pressed under a pressure of 200 MPa. It was then sintered in a high-temperature furnace at 1250°C in air atmosphere for 6 hours, with a sample heating rate of 5°C / min. Finally, it was cooled to room temperature with the furnace to obtain a temperature-stable ceramic capacitor dielectric material for energy storage.

[0053] Silver electrodes were sintered onto both sides of the sintered ceramic dielectric material to form a disc capacitor. The relative permittivity of the dielectric material as a function of temperature was then tested and calculated. Figure 3 As shown, within the temperature range of -55 to 200℃, Sr 1.8 2Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15 The capacitance change rate does not exceed ±15%, meeting the X9R standard. For example... Figure 5 As shown, Sr 1.82 Ba 0.165 Sm 0.015 NaMn 0.015 Nb 4.985 O 15 Its energy storage density is 3.62 J / cm³. 3 The efficiency is 77.7%.

[0054] Example 4

[0055] Raw materials SrCO3, BaCO3, Sm2O3, Na2CO3, MnO2, and Nb2O5, all with a purity of 99.99%, were prepared in a stoichiometric ratio as follows: Sr 1.81 Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15The raw materials were placed in a ball mill jar and ball-milled in a high-energy ball mill using zirconia balls as the milling medium. The added raw material was 8% of the mass of the milling balls. The mixing and milling time was 6 hours, the rotation speed was 300 rpm, and the milling medium was anhydrous ethanol. The resulting product was dried in an oven at 120°C for 4 hours, and then pre-sintered at 1000°C for 4 hours at a heating rate of 5°C / min. The pre-sintered powder was then removed, ground, and then ball-milled again at anhydrous ethanol as the milling medium for 6 hours to mix evenly. After drying at 120°C for 4 hours, it was ground into powder, pressed into discs, and then cold isostatically pressed under a pressure of 200 MPa. The sample was sintered in a high-temperature furnace in an air atmosphere at 1250°C for 6 hours, with a heating rate of 5°C / min. Finally, it was cooled to room temperature with the furnace. This yielded a temperature-stable ceramic capacitor dielectric material for energy storage.

[0056] Silver electrodes were sintered onto both sides of the sintered ceramic dielectric material to form a disc capacitor. The relative permittivity of the dielectric material as a function of temperature was then tested and calculated. Figure 3 As shown, within the temperature range of -55 to 200℃, Sr 1.8 1Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15 The capacitance change rate does not exceed ±15%, meeting the X9R standard. For example... Figure 5 As shown, Sr 1.81 Ba 0.17 Sm 0.02 NaMn 0.02 Nb 4.98 O 15 Its energy storage density is 2.42 J / cm³. 3 The efficiency is 86.7%.

[0057] The above results show that the Sr of the present invention 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 (x = 0.005, 0.01, 0.015 or 0.02) Ceramic capacitor dielectric materials can be used as temperature-stable ceramic capacitor dielectric materials.

[0058] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A ceramic capacitor dielectric material for energy storage, characterized in that, The chemical formula of the ceramic capacitor dielectric material is Sr. 1.85-2x Ba 0.15+x Sm x NaMn x Nb 5-x O 15 Where x takes the values ​​0.005, 0.01, 0.015, or 0.02; The method for preparing the dielectric material of the ceramic capacitor for energy storage is characterized by comprising the following steps: (1) A mixture containing SrCO3, BaCO3, Sm2O3, Na2CO3, MnO2 and Nb2O5 was ball-milled and dried in sequence to obtain sample I; (2) Press the sample I into shape and pre-fire it to obtain sample II; (3) Grind the sample II, and then successively perform ball milling, drying, pressing, cold isostatic pressing, sintering, and cooling to room temperature to obtain the ceramic capacitor dielectric material for energy storage.

2. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, The capacitance change rate of the dielectric material of the ceramic capacitor is 15%.

3. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, In step (1), the molar ratio of Sr, Ba, Sm, Na, Mn, Nb and O elements in the mixture is (1.85-2x):(0.15+x):x:1:x:(5-x):15, where x takes the value of 0.005, 0.01, 0.015 or 0.

02.

4. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, In steps (1) and (3), anhydrous ethanol is used as the ball milling medium. The rotational speed of the ball mill is independently 250~350 r / min; The ball milling time is independently 5 to 7 hours.

5. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, In steps (1) and (3), the drying temperature is 100~150℃; The drying time is 3 to 5 hours.

6. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, In step (2), the pre-firing temperature is 800~1200℃; The preheating time is 3-5 hours.

7. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, In step (3), the pressure of the cold isostatic pressing is 150~250MPa.

8. The ceramic capacitor dielectric material for energy storage according to claim 1, characterized in that, In step (3), the sintering temperature is 1230~1250℃; The sintering time is 5-10 hours; The heating rate of sample II during the sintering process is 4~6℃ / min.

9. An application of a ceramic capacitor dielectric material for energy storage as described in claim 1 or 2, characterized in that, Ceramic capacitor dielectric materials are used in the fabrication of capacitors for energy storage.

Citation Information

Patent Citations

  • X8R type ceramic capacitor dielectric material and preparation method thereof

    CN110511026A

  • Multilayer ceramic capacitor and method of producing the same

    US20060198078A1